The Policy Implementation of Street Children’s Handling in Serang City, Banten Province - Titi Stiawati; Ika Arinia Indriyany (Universitas Sultan Ageng Tirtayasa, 2022)
This research is directed to know, understand and describe the actual situation in the field in detail and actual about the standards and objectives of policy implementation in handling street children in Serang City Banten Province. Therefore, the research method used in this study is qualitative methods. This research shows that every activity carried out by the government has a legal basis for reference in acting. In addition, the existence of a legal basis shows the existence legitimacy of the community to the government to carry out its functions as government administrators. The purpose of a legal basis in government activities is to prevent deviant actions that can harm the community. So the Serang City Regional Regulation Number 2 of 2010 is the basis for the Serang City Government in implementing the handling of street children in Serang City. However, the standards and targets of policy implementation are not yet appropriate because the regulations only regulate children, in general, do not explicitly regulate the handling of street children.